Gaseous and soil OCPs and PCBs along the Indus River, Pakistan: spatial patterns and air-soil gradients - Sohail, Muhammad; Musstjab Akber Shah Eqani, Syed Ali; Ilyas, Shazia; Bokhari, Habib; Ali, Nadeem; Podgorski, Joel E; Muhammad, Shafi; Adelman, Dave; Lohmann, Rainer (Environmental science--processes & impacts, 2023)
This study presents first-hand information on the occurrence of persistent organic pollutants (POPs) in the ambient air and surface soil along the Indus flood-plain, Pakistan. The sampling campaign was conducted at 15 site locations during 2014-15, along the Indus River (approximately 1300 km). Composite surface soil samples ( N = 15) and passive air samples ( N = 15) were collected for the estimation of gaseous POPs as well as air-soil exchange to evaluate the POP emission and distribution or dispersion patterns, source tracking, and contribution of the local and regional sources towards POP accumulation in the Indus River system. Among the studied POPs, levels of DDTs and PCBs were noticeably higher in ambient air (50-560 and 10-1100 pg m −3 ) and in soil (0.20-350 and 1.40-20 ng g −1 ), respectively. Regarding the spatial patterns, higher DDT concentrations (ng g −1 ) were detected in the air and soil samples collected from the wet mountain zone (WMZ) ( p < 0.05), followed by the alluvial riverine zone (ARZ), low-lying mountain zone (LLZ), and frozen mountain zone (FMZ). The PCB data did not exhibit significant differences ( p > 0.05) for the air samples, while PCB concentrations were significantly higher ( p < 0.05) in soil from the LLZ, which may be associated with rapid urbanization and industrial activities in this area. The air-soil exchange of DDTs and PCBs showed net volatilization at most of the studied sites except for a few samples from the FMZ and WMZ. Results of this study about air-soil exchange gradients indicate the long range regional atmospheric transport (LRAT) of POPs to the colder areas (FMZ) of Pakistan, where these act as a secondary source of POPs in these areas. Results of this study indicate the contribution of regional as well local sources towards long range atmospheric transport (LRAT) of persistent organic pollutants (POPs) to the colder areas of Pakistan, where these act as a secondary source of POPs.